Kritisk politisk etik - Carl-Henric Grenholm (Svensk Teologisk Kvartalskrift)
This article gives a critical analysis of four different theories on the relationship between politics and morality. One is political cynicism, according to which the political sphere has nothing to do with morality. A second theory is political realism, which argues that the moral norms that are relevant in politics are different from those valid for the relationship between individual persons. The third theory is political moralism, according to which moral considerations should have a direct impact on the actions of political agents.